Socio-technical dynamics of XBRL extensions in Europe: an analysis of digital corporate reporting practices - Zvekan, Goran (Journal of Financial Reporting and Accounting, 2025)
Purpose This paper aims to investigate the factors shaping the creation process of digital corporate reports in Europe, focusing on the interplay between organisational, regulatory and socio-technical factors in influencing eXtensible Business Reporting Language (XBRL) practices. Design/methodology/approach Using a data set of 2,448 European Single Electronic Format filings from 2020 to 2023, this study adopts an interpretive approach to analyse extension ratios, anchoring practices and the role of third-party service providers. The socio-technical framework is used to explore the empirical interactions between organisational constraints and regulatory pressures during the tagging process. Findings The results reveal that smaller firms may experience greater challenges in complying with regulatory requirements, as evidenced by higher extension ratios. In addition, reliance on third-party service providers is associated with a higher likelihood of unnecessary extensions, potentially undermining report quality. Moreover, 14.1% of filings contain unanchored elements, complicating report comparability and increasing complexity. Originality/value This paper contributes to the limited literature on XBRL reporting in Europe by integrating socio-technical theory to provide novel insights into preparers’ tagging behaviours and anchoring practices in digital corporate reports. It highlights the need for regulators to consider organisational constraints and the role of external actors in shaping digital reporting practices. This study provides practical implications for regulators, preparers and users of digital corporate reports, emphasising a regard for the socio-technical dynamics influencing report quality and comparability
Keywords: Digital Corporate Reporting; XBRL; ESEF; Socio-technical theory; Service Provider